Carotid intimal medial thickness in children with celiac disease - Bhavika, Y M; Dewan, Vivek; Sachdev, Namrita; Yadav, T P; Mittal, Hema; Yadav, Ajeet Kumar; Nabum, Surat (Indian Journal of Child Health, 2019)
Introduction: Increasing cardiovascular risk in celiac disease (CD) may be attributed to the chronic systemic inflammation and unfavorable biochemical profile leading to accelerated atherosclerosis. Carotid intimal medial thickness (CIMT) has emerged as a direct marker of the early atherosclerosis as compared to traditional biochemical markers. Objectives: The aim of this study was to evaluate the CIMT in children with CD aged 1–16 years. Materials and Methods: A cross-sectional observational study was conducted at the department of Pediatrics and Radio Diagnosis in a tertiary care hospital of New Delhi. Thirty-six children with CD with age- and sex-matched controls were enrolled. CIMT for the anterior and posterior walls on each side was measured, and the mean CIMT was obtained for all the enrolled children. Results: The mean right-sided CIMT was significantly higher in cases (0.053±0.009 cm vs. 0.039±0.007 cm, p=0.000). The mean left-sided CIMT did not significantly differ between the groups (0.051±0.009 cm vs. 0.048±0.055 cm, p=0.702). The mean CIMT (right and left together), although higher in Celiacs, was not significantly different from controls (0.052±0.008 cm and 0.044±0.029 cm, p=0.114). However, a significant positive correlation between the age of the patients, age at the onset of symptoms, and CIMT was noted. Conclusion: Although we could not demonstrate statistically significant results, the mean CIMT and the right-sided measurements were significantly higher in cases than in controls.